Models of reablement evaluation (MoRE): a study protocol of a quasi-experimental mixed methods evaluation of reablement services in England. Issue 1 (December 2016) - Mann, Rachel; Beresford, Bryony; Parker, Gillian; Rabiee, Parvaneh; Weatherly, Helen; Faria, Rita; Kanaan, Mona; Laver-Fawcett, Alison; Pilkington, Gerald; Aspinal, Fiona
Abstract Background Reablement is a time-limited intervention that aims to support people to regain independence and enable them to resume their daily activities after they return home from an in-patient care setting, or to maintain independence to enable them to remain at home. There is some evidence that reablement can enhance independence and has the potential to contain costs. However, reablement services are funded and provided in different ways and by different organisations, and there is limited research evidence about the effectiveness of different reablement service models. This study will evaluate the effectiveness and cost-effectiveness of different reablement service models and service users' and carers' experiences of reablement in England, UK. Methods/Design The study will use a quasi-experimental mixed methods design that comprises three work packages (WP) extending over a period of 34 months. WP1 will conduct cluster analysis on survey data to develop a typology of current models of reablement services in order to describe the current reablement service landscape. WP2 will comprise a quantitative outcomes evaluation of the effectiveness of the different service models; a process evaluation and an economic evaluation. WP2 will be set within generic reablement services, where providers are using the most commonly employed generic reablement service types identified in WP1; the primary outcome measure is health-related quality of life measured by the EQ-5D-5L. WP3 will provide evidence about specialist reablement services and how specialist approaches and practices are organised and delivered. Discussion Managing demands on care services is, and will remain, a crucial factor for the UK National Health Service as the number of people with long-term conditions rise. There has been, and will continue to be, significant investment in reablement services. The proposed study will address several key areas where there is limited evidence regarding the organisation and delivery of reablement services in England, UK. Specifically, it will provide new evidence on different models of reablement services that will be of direct benefit to health and social care managers, commissioners and their partner organisations.